Prevalensi penderita Bunion pada guru dan pegawai wanita di delapan SMA Negeri di Denpasar yang menggunakan sepatu hak tinggi - Putu Paramita Primadevi Pramana; Yuliana Yuliana; Muliani Muliani (Bali Anatomy Journal, 2019)
Background: High school’s female teachers and staff are often using high heels that can cause health problem, bunion. Aim: This study aims to determine the prevalence of bunion sufferers among female teachers and employees in eight public high schools in Denpasar who use high heeled shoes. Method: This study was a cross-sectional descriptive study, involve 80 samples. In collecting data the writer used questionnaires and feet photos. The data was taken in 8 public high schools in Denpasar. Data were analyzed with SPSS 24. Result: Of the 80 samples, 25 suffered from bunion. The proportion of patients with underweight is 0%, normal is 31.1%, overweight is 33.3%, obesity is 37.5%. Patients with heels <4cm 14.3%, 4 - 7 cm 43.2%, and >8 cm 100%. Patients with stiletto heel’s type is 50%, moderate is 29.9%, wide is 28.6%. Patients with usage period >12 years is 38.9%, ≤ 12 years is 25%. Patients with usage duration >3 hours is 31.6%, ≤ 3 hours is 0%. Patients with risk activities is 32.9%, without is 14.3%. Patients with pain complaints is 26.7%, without is 37.1%. Conclusion: the prevalence of bunion sufferers is 31.25%. The proportion sufferers based on nutritional status dominated by obesity, based on the height of the heels dominated by the height of > 8 cm, based on heels type dominated by narrowed type, based on usage period dominated by >12 years, based on usage duration dominated by >3 hours, based on risk activities dominated by patients who have risky activities, based on complaints of pain dominated by patients who didn’t feel pain.